Erythromycin resistance of clinical Campylobacter jejuni and Campylobacter coli in Shanghai, China - Gao, Fen; Tu, Lihong; Chen, Mingliang; Chen, Hongyou; Zhang, Xi; Zhuang, Yuan; Luo, Jiayuan; Chen, Min (Frontiers in Microbiology, 2023)
Campylobacter species are zoonotic pathogens, as well as the prevalent cause of foodborne bacterial gastroenteritis. The spread of antimicrobial resistant strains poses a serious threat to global public health and attracts attention worldwide, but information about clinical Campylobacter is relatively limited compared to isolates from food and animals. The current study illustrated the prevalence and antimicrobial resistance profiles of Campylobacter jejuni and Campylobacter coli isolates collected from a consecutive surveillance program between 2012 and 2019 in Shanghai, China. Among the 891 Campylobacter strains (761 C. jejuni and 130 C. coli) isolates collected, high portions above 90% of resistance to ciprofloxacin, nalidixic acid, and tetracycline were observed for both C. jejuni and C. coli. The most common MDR profiles represented by C. jejuni and C. coli were combination of ciprofloxacin, tetracycline, florfenicol and nalidixic acid (5.39%), and azithromycin, ciprofloxacin, erythromycin, gentamicin, tetracycline, clindamycin, nalidixic acid (28.46%), respectively. The erythromycin resistance of C. coli (59.23%) is higher than C. jejuni (2.50%). A total of 76 erythromycin resistant isolates (16 C. jejuni and 60 C. coli) were sequenced using Illumina platform for determining the genotypes, antimicrobial resistance patterns and phylogeny analysis. Multilocus sequence typing (MLST) analysis showed a high genetic diversity with 47 sequence types (STs), including 4 novel alleles and 12 new STs. The most abundant clonal complexes (CCs) were CC-403 (31.25%) and CC-828 (88.33%) for C. jejuni and C. coli, respectively. Among the 76 erythromycin resistant isolates, mutation A2075G in 23S rRNA and erm(B) gene were detected in 53.95% and 39.47%, respectively. The erm(B) gene was identified exclusively in 30 C. coli isolates. All these erm(B) positive isolates were multi-drug resistant. Furthermore, comparison of the erm(B)-carrying isolates of multiple sources worldwide demonstrated the possibility of zoonotic transmission of erm(B) in Campylobacter. These findings highlight the importance of continuous surveillance of erythromycin resistance dissemination in Campylobacter which may compromise the effectiveness of antimicrobial therapy.